Transmission Dynamics of Dengue Disease in the Rupandehi District of Nepal - Gautam, Dwarika Prasad; Gautam, Ramesh; Adhikari, Khagendra; Pokharel, Anjana; Uprety, Kedar Nath (Journal of Nepal Mathematical Society, 2024)
Increasing incidence of dengue fever has become an important health concern in recent years, especially in developing country like Nepal. To investigate patterns of transmission, this work uses a mathematical model for the dynamics of dengue outbreaks in the Rupandehi district in 2017. To validate the model biologically, we demonstrate the positivity and boundedness of solutions. Furthermore, we establish that for R0 < 1, the disease-free equilibrium is locally asymptotically stable, whereas for R0 > 1, a unique endemic equilibrium point exists. Sensitivity analysis showed that the parameters related to mosquitoes, in particular the mosquito death rate (µv) and mosquito biting rate in transmission rates (β1, β2, βv), have signifcant impact on R0. Therefore, implementing mosquito control activities followed by protection against mosquito bites are crucial strategies in effectively controlling dengue transmission.